Trace metals in the livers of marine mammals from the Welsh coast and the Irish Sea - Law, R. J.; Jones, B. R.; Baker, J. R.; Kennedy, S.; Milne, R.; Morris, R. J. (Marine Pollution Bulletin, 1992)
Samples of liver from forty-two marine mammals of six species found on the coast of Wales and the Irish Sea in 1989-1991 have been analysed for a range of trace metals (Cr, Ni, Cu, Zn, Cd, Hg, and Pb). The animals sampled comprised eleven seals, twenty-two porpoises, eight dolphins and one Minke whale. The range of concentrations for each metal were, in μg g wet wt: Cr